Degradation mechanism of AISI 316L, 321H, and 347H alloys in ternary molten salt vs solar salt - J. Chaves; M.I. Lasanta; G. García-Martín; M.T. de Miguel; F.J. Pérez (Results in Engineering)
This study aims to evaluate the corrosion behavior of AISI 316L, 321H, and 347H stainless steels in Solar salt (60 % NaNO₃ + 40 % KNO₃) and a ternary molten salt (52 % NaNO₃ + 35 % KNO₃ + 13 % LiNO₃) at 580 °C. The importance of this work lies in understanding corrosion mechanisms and optimizing salt compositions for improved material durability and thermal performance. Results showed that 347H exhibited the lowest corrosion rates, 0.035 mm/y in Solar salt and 0.027 mm/y in ternary salt, outperforming 316L and 321H in both environments. The ternary salt demonstrated a higher thermal operating range (373.23 °C vs. 312.28 °C for Solar salt), offering potential advantages for CSP applications.